Mathematically analysis on two stroke uniflow scavenging system - Mohd Zaimatulakmar, Abdullah (2007)
Conventional 2-stroke engines are commonly used for two-wheeled and marine vehicles that have small engine displacement. However problems such as unstable combustion, high fuel consumption rate, high hydrocarbon (HC) emission need to be resolved. Beside that, the two stroke engines also have its advantages over the four stroke engines such as higher torque and power, being more compact and lighter. In order to solve these problems without compromising these advantages, a new 2-stroke engine was designed with numerical simulations to produce what is called a two stroke engine uniflow scavenging system. In this study, the performance of the uniflow scavenging engine was researched, and considerations concerning fuel consumption and exhaust gas emissions were made. These findings were then compared with the earlier research to consider gas flow and diffusion of fuel inside the cylinder. This study also describes the effects of the scavenging ports configuration to the flow pattern, the scavenging efficiency and the scavenging pressure, in case of uniflow scavenging two-stroke engine. In this research we will analyses all the parameters of the two stroke uniflow scavenging system based on of the geometry of the intake and exhaust port design, by applied mathematical formulas using of graphical dynamic system simulation software which is MatLab.